2022
DOI: 10.26434/chemrxiv-2022-v1989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biolistic Delivery of MOF-Protected Liposomes

Abstract: Needle-and-syringe-based delivery has been the commercial standard for vaccine administration to date. With worsening medical personnel availability, increasing biohazard waste production, and the possibility of cross-contamination, we explore the possibility of biolistic delivery as an alternate skin-based delivery route. Delicate formulations like liposomes are inherently unsuitable for this delivery model as they are delicate biomaterials incapable of withstanding shear stress. When encapsulated within a cr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Liposomes were synthesized and encapsulated in ZIF using a previously published protocol (encapsulation with 20 mM zinc acetate and 640 mM 2-methylimidazole). [25]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomes were synthesized and encapsulated in ZIF using a previously published protocol (encapsulation with 20 mM zinc acetate and 640 mM 2-methylimidazole). [25]…”
Section: Methodsmentioning
confidence: 99%
“…[11, 12] ZIFs are unique as polymeric materials due to their kinetic lability; phosphate and carbonate salts, or albumin-rich environments readily pull the zinc from the framework causing it to dissolve completely, returning the original antigen to its pristine state. [13, 14] ZIF’s versatility in capturing, preserving, and releasing antigens is exceptional and has been used to encapsulate whole viruses,[15, 16] bacteria,[17] proteins,[18, 19] DNA,[20, 21] RNA,[22] yeast,[23] liposomes,[24, 25] enzymes,[26, 27] glycans,[28] and carbohydrates. [29] We have recently shown that ZIF-encapsulated formulations exhibit a depot effect, which significantly enhances the efficacy of vaccine models.…”
Section: Introductionmentioning
confidence: 99%